Paraguay : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2011)
Paraguay's economy recently experienced particularly large output swings. Economic policies will play a critical role in raising investment by making sure that macroeconomic stability is maintained. The spillovers from the agricultural sector to the rest of the economy are limited. The high level of bank excess reserves in Paraguay reflects a mixture of precautionary and involuntary factors. Large bank excess reserves weaken the monetary transmission channel, and cause inefficiency costs. Bank reforms should be undertaken to preserve financial and macroeconomic stability.